ANALISIS INVESTASI DAN PENENTUAN PORTOFOLIO SAHAM OPTIMAL DENGAN METODE INDEKS TUNGGAL (STUDI EMPIRIS PADA IDX 30 YANG TERDAFTAR DI DI BURSA EFEK INDONESIA PERIODE AGUSTUS 2017-JANUARI 2018) - Mulyati, Sri; Murni, Ania (Department of Accounting, Faculty of Economics & Business, 2018)
This study aims to analyze investment and determine the optimal stock portofolio with single indexs method. The data used in this study is secondary data obtained from 30 idx 30 companies accessed on www.idx.co.id, www yahoofinance.co.id, adnd www.bi.go.id, and obtained through documentation and library research study techniques. This study uses a descriptive research method with a quantitative approache. The results of this study indicate that there are seven optimal companies because the ERB(expected return to beta) values are higher than the CI value of LPKR, PGAS, PTPP, SMGR, SRIL, UNTR AND SMGR.